Genetics and Genomics of the Brassicaceae - Fujimoto, Ryo; Takada, Yoshinobu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Brassica includes economically important vegetables. This Special Issue aims to provide a comprehensive overview of genomics and genetic analysis in Brassicaceae. There is particular interest in research on agronomically important traits.